PROMOSI KESEHATAN UPAYA MENINGKATKAN KAPASITAS FISIK PADA LANSIA DI KEL. BUKIT SOFA KEC. SIANTAR SITALASARI - Isa Harpika Br. Ginting; Noni Herawati; Febrina Sani Saragih (Yayasan Nusantara Hasana Berdikari, 2023)
This study aimed to improve the physical capacity of older adults in Bukit Sofa Village, Siantar Sitalasari District, through a structured physical exercise intervention and nutrition education. Older adults are vulnerable to declining physical capacity, malnutrition, and frailty, which negatively affect quality of life and increase morbidity and mortality. A 12-month community-based quasi-experimental intervention study was conducted with participants aged ≥60 years. The intervention included multimodal physical training (strength, balance, flexibility, and aerobic activity) performed three times per week for 60 minutes per session, along with nutrition education based on the WHO ICOPE guideline and basic function screening using the SKILAS tool. Pre- and post-intervention evaluations were conducted using the Short Physical Performance Battery (SPPB), Senior Fitness Test (SFT), and anthropometric measures (BMI and WHR). Results showed significant improvements in muscle strength, flexibility, balance, and aerobic capacity, as well as a reduced risk of frailty and malnutrition. The program’s effectiveness was supported by the involvement of caregivers and community leaders.